INSECT POPULATIONS, PESTS AND BENEFITS IN COTTON SOCAS ON THE ATLANTIC COAST. METHODS AND TIMES OF DESTRUCTION - CARDONA, CÉSAR; PACHECO, LUIS CARLOS; RENDÓN, FRANCISCO (Revista Colombiana de Entomología, 1979)
Studies on the effect of ratton cotton on insect populations were carried out in six cotton-growing areas of Northern Colombia. The experiments were conducted between 1976 and 1978. It was found that between harvesting (February) and the second week of March, insect pests occurred in low numbers on ratoon cotton. Parasites and predators were abundant. Aphids, cotton stainers, leafhoppers, and bollworms were not important. The pink bollworm, Pectinophora gossypiella (Saunders) and the boll weevil, Anthonomus grandis Boheman, appeared in low numbers towards the third week of April; their populations increased sharply towards the second week of May and were considered a very important threat for the following season. Based on the population dynamics of these pests it was concluded that crop residues should be completely destroyed by May 1 st. and that the post-free period should be extended for at least 75 days. Plowing under stalks and debrisis the most efficient method to destroy harvest residues. Shredding facilitates plowing, but if plowing is delayed after shredding the old plant stubs will grow new sprouts which favor high infestations of Alabama argillacea (Hubner), the boll weevil and Bucculatrix thurberiella Busck.